AVALIAÇÃO DA INFLUÊNCIA DO ADITIVO HIDROFUGANTE NAS PASTAS DE GESSO DE FUNDIÇÃO - Silva, Daniel Bruno Pinto da; Sousa, José Getúlio Gomes de; Ferreira, Davison Caique Evangelista; Rodrigues, Tayná Mirelle Cavalcante (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Gypsum is a binder that is also used in civil construction in the manufacture of precast and masonry lining. Its application is justified due to the ease of production and molding, low cost, resistance to fire, possibility of being reused and due to be a constructive system that promotes the reduction of loads. However, because this material has high solubility in water, the use is restricted to indoor environments and where there is no direct and constant contact with water. In this context, it is necessary to use water-repellent additives in the production of gypsum precasting, creating a waterproofing system with materials that are more resistant to the action of water. Studies related to the use of water repellent additives in foundry gypsum are still incipient. This work evaluated the effects caused by the use of commercial water repellent additives on the properties of the casting plaster in the fresh state (picking times and heat of hydration) and in the hardened state (surface hardness and compressive strength). The analysis indicated the influence of the additives on the properties of the pastes, which often did not meet the normative criteria.